A Variation of the Cords of the Brachial Plexus on the Right and a Communication between the Musculocutaneous and Median Nerves on the Left Upper Limb: A Unique Case - Kirazlı, Özlem; Tatarlı, Necati; Ceylan, Davut; Hacıoğlu, Hüsniye; Uygun, Seda; Şeker, Aşkın; Keleş, Evren; Çavdar, Safiye (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
During routine anatomical dissection of the upper extremity of a 64-year-old cadaver for educational purposes, we observed variations in the brachial plexus on each side. On the right an anomaly of cord formation was present and on the left there was a communication between the musculocutaneous nerve (MCN) and median nerve (MN). On the right side the brachial plexus showed two trunks, superior (C5 and C6) and inferior (C7, C8, and T1); the middle trunk was absent. The superior trunk bifurcated into anterior and posterior divisions, the anterior division continued as the lateral cord forming the MCN. The posterior division gave off the subscapular branch. The inferior trunk trifurcated into radial, median, and ulnar nerves. The radial nerve gave off the axillary and thoracodorsal nerves. The ulnar nerve gave off the median cutaneous nerves of the arm and forearm. The median nerve received a small ascending branch from the MCN. On the right side, there was a communicating branch from the MCN to the MN in the lower third of the arm region. This communicating branch also gave rise to a muscular branch to the brachialis muscle and the lateral cutaneous nerve of forearm. No additional heads of the biceps brachii muscle were observed in either upper limb. Knowledge of the variations of the brachial plexus in humans can be valuable for operations of the shoulder joint and its repair for providing an effective block or treatment for anesthetists and also for explaining otherwise incomprehensible clinical signs for neurologists.
Keywords: variation; musculocutaneous nerve; median nerve